Pendampingan kegiatan posyandu di desa Payung kecamatan Bodeh dalammemberikan penyuluhan mengenai pencegahan penyakit Campak - Bahri, Risna Syaiful; Assabiq, Ahmad Ma’sum; Auliya, Ikrima; Khikmah, Nurul; Amalia, Sherly Irma; Supriadi, Teguh; Rokhmah, Ainur; Munisa, Widad Fatim; Kasubakti, Galuh; Lutfiyani, Dewi Tri; Libriana, Safira; Nahdhiyah, Nur; Fitriana, Erma; Ishaqi, Alfath Dzulqo Al (Presisi Jurnal Pengabdian Masyarakat, 2022)
Measles is a highly contagious disease and a major cause of child mortality in developing countries, including Indonesia. The incidence of measles is still high in some areas. This study aims to find a solution to overcome measles in Payung village, Bodeh district, Pemalang district. This research uses descriptive qualitative research. The data collection used in this research is observation and documentation. The population is all measles cases residing in the Payung village area, Bodeh sub-district, Pemalang Regency. From the results of the study, it was found that the solution to overcome measles in Payung village requires cooperation between all aspects of society to avoid measles. The community is expected to carry out measles immunization for their children, especially for those under 5 years of age.